Impact of board characteristics and gender diversity on research and development spending in Jordan - Dua’a Shubita; Majd Munir Iskandrani; Hadeel Boshmaf; Hadeel Yaseen; Mohammad Fawzi Shubita (Problems and Perspectives in Management, 2025)
This study undertakes an investigation into the nexus between board characteristics and research and development (R&D) investments within the specific context of Jordan. Employing a dataset comprising 24 small and medium enterprises (SMEs) operating in the service and manufacturing sectors and enlisted on the Amman Stock Exchange (ASE) throughout the period from 2010 to 2023, the empirical findings substantiate that the dimensions of the board, mainly board size and independence, exert a positive influence on the intensity of R&D expenditures. However, gender diversity exerts an inverse impact on R&D spending. Consequently, organizations with a tendency toward sustaining innovation endeavors are encouraged to accord heightened consideration to fostering gender diversity during the board selection process. However, CEO duality reveals an insignificant influence on R&D expenditures. To conclude, the study’s outcomes enrich the existing array of findings on the influence of women directors on board independence, particularly in R&D spending. Furthermore, the study offers policy recommendations, enhancing comprehension of the influence of women’s representation on R&D spending.